Macroporous cryogel based spin column with immobilized concanavalin A for isolation of glycoproteins - Krenkova, Jana; Cesla, Petr; Foret, Frantisek (Electrophoresis, 2015)
In this work we have developed a hydrophilic poly(hydroxyethyl methacrylate-co-poly(ethylene glycol) diacrylate) cryogel placed in the centrifugal filter device. The composition of the polymerization mixture as well as the polymerization conditions were optimized in order to prepare a material with bimodal pore size distribution with 20-50 μm flow through macropores and submicrometer pores in the polymer walls. The optimized, mechanically stable, highly porous, material was used for spin column lectin chromatography. The surface of the monolithic scaffold was activated by epichlorohydrin and used for immobilization of concanavalin A to provide the affinity supports for selective isolation of glycoproteins containing high mannose glycan structures. The performance of the developed lectin modified cryogels was evaluated by analyses of glycoprotein mixtures. The efficiency and selectivity of the affinity supports were confirmed by MALDI-MS analysis.
Keywords: glykoproteiny; Cryogels; Polyethylene Glycols; polymerizace; polyethylenglykoly; Methacrylates; spektrometrie hmotnostní - ionizace laserem za účasti matrice; konkanavalin A; Chromatography, Liquid; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Concanavalin A; Glycoproteins; Polymerization; methakryláty; chromatografie kapalinová; kryogely